The Effects of Ascorbic Acid on Lipid Oxidation during the Processing of Mytilus edulis chilensis in the Beagle Channel (Tierra del Fuego) - Hernando, Marcelo Pablo; Malanga, Gabriela Fabiana (Nova Science Publishers, 2018)
Fil: Hernando, Marcelo Pablo. Comisión Nacional de Energía Atómica; Argentina